2016
DOI: 10.1017/s136898001600104x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a tax on sugar-sweetened beverages according to socio-economic position: a systematic review of the evidence

Abstract: Based on the available evidence, a tax on SSB will deliver similar population weight benefits across socio-economic strata or greater benefits for lower SEP groups. An SSB tax is shown to be consistently financially regressive, but to a small degree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(154 citation statements)
references
References 43 publications
(118 reference statements)
7
146
0
1
Order By: Relevance
“…SSB taxes are considered by some to be regressive, because low SES groups would be those most adversely affected financially 24 . As such, it was interesting that SES was not associated with support for a tax in our study.…”
Section: Discussionmentioning
confidence: 63%
“…SSB taxes are considered by some to be regressive, because low SES groups would be those most adversely affected financially 24 . As such, it was interesting that SES was not associated with support for a tax in our study.…”
Section: Discussionmentioning
confidence: 63%
“…taxes on high-fat foods or bans on fast-food advertising). A recent systematic review suggested that a tax on sugar-sweetened beverages will deliver similar population weight benefits across socioeconomic groups or greater benefits for lower socioeconomic groups [78]. This is generally supported by another review that found evidence for upstream interventions (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…Also, there is little information available on the average impacts of a SSB tax on untaxed beverages, and whether purchases and dietary intake of potential substitute beverages such as water or other untaxed beverages are increased. It was expected that SSB taxes would result in greater consumption of untaxed beverages (eg, juice, water, milk, and diet soft drinks), as demonstrated in price elasticity modelling studies . However, evidence from evaluation studies has not always been consistent and further examination is warranted.…”
Section: Introductionmentioning
confidence: 99%